(untitled) (Nexo Revista Científica, 2019)
In this paper the study of erosivity rainfall factor in the Xolotlán Lake sub catchment is exposed, that belong to the 9525 catchment from Nicaragua. The objective of the study was to determinate the Revised Universal Loss Equation (RUSLE) erosivity factor”, from daily pluviograph data of the station 69027 (Managua Airport) and monthly pluviometric data in 7 stations distributed in the sub catchment and nearby. A simple lineal regression was done with the monthly R and monthly precipitation, with a correlation coefficient of r2 = 0.86. Since in the sub cathcment there is only one pluviograph station, the Modified Fournier Index was used to estimate de R values in the pluviometrics stations. The study suggests that the annual mean erosivity factor rage from 5,000 Mj mm / (ha-h-year) in the lower side of the sub catchment to 7,250 in the upper side, that represent a rain with a moderate erosivity power.